COVID-19 Is a Multi-Organ Aggressor: Epigenetic and Clinical Marks - Kgatle, Mankgopo Magdeline; Lawal, Ismaheel Opeyemi; Mashabela, Gabriel; Boshomane, Tebatso Moshoeu Gillian; Koatale, Palesa Caroline; Mahasha, Phetole Walter; Ndlovu, Honest; Vorster, Mariza; Rodrigues, Hosana Gomes; Zeevaart, Jan Rijn; Gordon, Siamon; Moura-Alves, Pedro; et al. (Frontiers in Immunology, 2021)
The progression of coronavirus disease 2019 (COVID-19), resulting from a severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection, may be influenced by both genetic and environmental factors. Several viruses hijack the host genome machinery for their own advantage and survival, and similar phenomena might occur upon SARS-CoV-2 infection. Severe cases of COVID-19 may be driven by metabolic and epigenetic driven mechanisms, including DNA methylation and histone/chromatin alterations. These epigenetic phenomena may respond to enhanced viral replication and mediate persistent long-term infection and clinical phenotypes associated with severe COVID-19 cases and fatalities. Understanding the epigenetic events involved and their clinical significance may provide novel insights valuable for the therapeutic control and management of the COVID-19 pandemic. This review highlights different epigenetic marks potentially associated with COVID-19 development, clinical manifestation, and progression.